If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + -2) + 19 = (5x + -1)(1 + -5x) Reorder the terms: 10(-2 + x) + 19 = (5x + -1)(1 + -5x) (-2 * 10 + x * 10) + 19 = (5x + -1)(1 + -5x) (-20 + 10x) + 19 = (5x + -1)(1 + -5x) Reorder the terms: -20 + 19 + 10x = (5x + -1)(1 + -5x) Combine like terms: -20 + 19 = -1 -1 + 10x = (5x + -1)(1 + -5x) Reorder the terms: -1 + 10x = (-1 + 5x)(1 + -5x) Multiply (-1 + 5x) * (1 + -5x) -1 + 10x = (-1(1 + -5x) + 5x * (1 + -5x)) -1 + 10x = ((1 * -1 + -5x * -1) + 5x * (1 + -5x)) -1 + 10x = ((-1 + 5x) + 5x * (1 + -5x)) -1 + 10x = (-1 + 5x + (1 * 5x + -5x * 5x)) -1 + 10x = (-1 + 5x + (5x + -25x2)) Combine like terms: 5x + 5x = 10x -1 + 10x = (-1 + 10x + -25x2) Add '1' to each side of the equation. -1 + 1 + 10x = -1 + 10x + 1 + -25x2 Combine like terms: -1 + 1 = 0 0 + 10x = -1 + 10x + 1 + -25x2 10x = -1 + 10x + 1 + -25x2 Reorder the terms: 10x = -1 + 1 + 10x + -25x2 Combine like terms: -1 + 1 = 0 10x = 0 + 10x + -25x2 10x = 10x + -25x2 Add '-10x' to each side of the equation. 10x + -10x = 10x + -10x + -25x2 Combine like terms: 10x + -10x = 0 0 = 10x + -10x + -25x2 Combine like terms: 10x + -10x = 0 0 = 0 + -25x2 0 = -25x2 Solving 0 = -25x2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25x2' to each side of the equation. 0 + 25x2 = -25x2 + 25x2 Remove the zero: 25x2 = -25x2 + 25x2 Combine like terms: -25x2 + 25x2 = 0 25x2 = 0 Divide each side by '25'. x2 = 0 Simplifying x2 = 0 Take the square root of each side: x = {0}
| (x-6)+(x^2+14)= | | 19X=57/49 | | 3x+8=4-9 | | 5/3X=25/27 | | 15+3=17-t | | 5t-7=t+13 | | ((x-1)/6)-((x-3/2))=-1 | | a(x+1)+5a(x-1)=2(2b-2a) | | (6x^2y-4xy)+(8x^2y-5xy)= | | 63=37x+22 | | 4(2x-3)+5(3x-4)=16 | | 0=x-100+30-20 | | x=sqrt(50u^12v^8) | | sqrt(50u^12v^8)= | | x=.06(149600+x) | | 2x+5-y=12 | | 5/11=x/16 | | -3+2r+7r+4+8r= | | 4x-3/5=6x/7-1 | | (5x^3+2)(x^2-2)= | | y=t^3-14t^2+50t | | 4x5-3=6x/7-1 | | (x+10)(x^2-10x+100)= | | 2ex+2=5 | | (7x^3-9x^2+4x-4)-(3x^3-2x^2-6x+4)= | | 7=0.5a | | a=(bc/2x) | | t=(pd/2x | | 6x^2-x^2-7=0 | | (6x+2)(3x-4)= | | -7d-3+3d-4d-4d= | | (2x+4)(4x+6)= |